Histopathological spectrum of upper gastrointestinal endoscopic biopsies - Hirachand, Suspana; Sthapit, RR; Gurung, P; Pradhanang, S; Thapa, R; Sedhai, M; Regmi, S (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Upper gastrointestinal tract disorders are one of the most commonly encountered problems in the clinical practice. A variety of disorders can affect the upper gastrointestinal tract. Endoscopy, in combination with biopsy, plays an important role in the exact diagnosis for further management.Objectives: To determine the spectrum of histopathological lesions of upper gastrointestinal tract.Methods: A prospective study was conducted in the Department of Pathology, Kathmandu Medical College and Teaching Hospital, Nepal from January 2015 to December 2016 (2 years).Results: A total 243 endoscopic biopsies were evaluated. Out of which, 219 cases were from gastric, 15 were from esophagus and 9 were from duodenum. Among the gastric biopsies, 77 cases (35.16%) were chronic active gastritis and 27 cases (12.33%) were malignant. The most common malignancy was adenocarcinoma. Among the 15 oesophageal biopsies, 12 cases (80%) were of non-neoplastic and 3 cases (20%) were of neoplastic nature. The most common malignancy was squamous cell carcinoma. Among 9 cases of duodenum biopsies, all were non-neoplastic, of which chronic non-specific duodenitis (66.66%) was the commonest.Conclusion: Endoscopy is incomplete without histopathological examination of biopsy and so, the combinations of methods play an important role in diagnosis and management of upper gastrointestinal tract disorders.Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, Page: 67-74